The Impact of Economic and Social Factors on the Collapse of the Abbasid Caliphate Army 512 - 656 A H - 1118 - 1258 AD (Islamic Sciences Journal, 2026)
There are several economic and social factors, in addition to the political factors that were formed by the weakness of some of the Abbasid caliphs, and they    became fundamental factors in the decline, decline, and disintegration of the Abbasid army. These factors were deeply rooted in the body of Abbasid creativity, which led to its collapse, that is, its weakness and disintegration. Among the economic factors is the secession of the states .There are several economic and social factors that had a deep impact on the body of the Abbasid Caliphate, which led to its weakness and disintegration, including the separation of states and its impact on the economy of the Caliphate’s imports, natural disasters, floods, and the governors’ and leaders’ monopolization of wealth and fiefdoms. As for the social factors, including living conditions, the high level of prices, the abundance of strife and unrest, the emergence of entertainment and heresy, and the emergence of the Shattar and Fiqar movement, all of these factors. It led to the collapse of the army of the Abbasid Caliphate in (656/512) .
Keywords: Caliphate, Army, Governors, Wages .